Invasive Assessment of Hemodynamic, Metabolic and Ionic Consequences During Blood Flow Restriction Training - Franz, Alexander; Berndt, Felix; Raabe, Joachim; Harmsen, Jan-Frieder; Zilkens, Christoph; Behringer, Michael (Frontiers in Physiology, 2020)
Purpose: Medically recommended training often faces the dilemma that necessary mechanical intensities for muscle adaptations exceed patients' physical capacity. In this regard, blood flow restriction (BFR) training is becoming increasingly popular because it enables gains in muscle mass and strength despite using low-mechanical loads combined with external venous occlusion. Since the underlying mechanisms are still unknown, we applied invasive measurements during exercise with or without BFR to promote physiological understanding and safety of this popular training technique. Methods: In a randomized cross-over design, ten healthy men (28.1±6.5 years) underwent two trials of unilateral biceps curls either with (BFR) or without BFR (CON). For analysis of changes in intravascular pressures, blood gases, oximetry and electrolytes, an arterial and a venous catheter were placed at the exercising arm before exercise. Arterial and venous blood gases and intravascular pressures were analyzed before, during and 5 min after exercise. Results: Intravascular pressures in the arterial and venous system were more increased during exercise with BFR compared to CON (p<0.001). Furthermore, arterial and venous blood gas analyses revealed a BFR-induced metabolic acidosis (p<0.05) with increased lactate production (p<0.05) and associated elevations in [K+], [Ca2+] and [Na+] (p<0.001). Conclusion: The present study describes for the first time the local physiological changes during BFR training. While BFR causes greater hypertension in the arterial and venous system of the exercising extremity, observed electrolyte shifts corroborate a local metabolic acidosis with concurrent rises in [K+] and [Na+]. Although BFR could be a promising new training concept for medical application, its execution is associated with comprehensive physiological challenges.